IMPLEMENTASI JURNALISME PERSPEKTIF GENDER PADA PEMBERITAAN BURUH MIGRAN PEREMPUAN DI MEDIA ONLINE - Khairunnisa, Almira; Hasfi, Nurul; Nugroho, Adi (Interaksi Online, 2024)
Women are the gender group that dominates the number of migrant workers in Indonesia. The significant increase in the number of women among migrant workers is directly proportional to the increase in the number of cases experienced by migrant workers. Online media as a provider of public space to monitor the power and representation of minorities should be able to provide news with a positive climate for women through the implementation of gender perspective journalism. The results of the research show that online media in Indonesia has implemented most of the gender perspective journalism indicators through the proportion of sensational diction in news titles, the proportion of news bodies that meet the journalistic code of ethics adopted from articles 4, 5 and 8, the proportion of diction used in body of news, and the proportion of female and male sources in the news. Of the 63 news stories analyzed, 39 news stories (61.9%) had titles that contained some sensationalist diction, 33 news stories (52.4%) had implemented a journalistic code of ethics that was relevant to gender perspective rules, and 30 news stories (47.6%) had used diction that gender perspective. In the resource element, the research results showed that 60.5% of the resource persons were male, while 39.5% of the resource persons were female. However, the number of categories implementing some indicators and implementing all indicators is not significantly different in the category of using stereotypical diction in news titles and body of news. Thus, online media has a record of creating a more balanced proportion of reporting in terms of diction selection.